Об оценивании функционалов от решения линеаризованной задачи Навье-Стокса по неполным данным - Головач, В.Н.; Подлипенко, Ю.К. ("Доповіді НАН України", 2007)
We investigate the problem of minimax estimation of an unknown solution to the linearized Navier-Stokes problem under the assumption that unknown deterministic data of this problem, as well as the statistical characteristics of noises in observations, are subjected to certain quadratic restrictions.